Transformation of Safety Management in Mega Projects: Exploring the Impact of Smart Technology and Digitization on Performance and Safety in The Kingdom of Saudi Arabia - Barnawy, Mohammad Abdullah; Althaqafy, Samiyah Rafan; Batawi, Faris Omar (Journal of engineering sciences and information technology, 2025)
This study discusses a comparison between traditional safety management and smart safety management in light of digital transformations, focusing on major projects in Saudi Arabia, such as NEOM, the New Square, and the sports venues planned for the 2034 World Cup. The study aims to explore how modern technologies like artificial intelligence and the Internet of Things can improve safety standards and reduce risks. A descriptive analytical approach was adopted to collect data through surveys and interviews with safety management experts, in addition to analyzing related documents. Results showed that 75% of participants consider smart safety management more effective, contributing to improved efficiency and reduced accidents. However, key challenges were identified, such as high costs and cyber threats, which hinder the implementation of this management. The study emphasizes the necessity of applying smart safety management to ensure the success of major projects and achieve sustainability, recommending the development of strategies to address challenges related to costs and training.